Review of the species of Pelodiaetodes Moore (Coleoptera: Carabidae: Bembidiini: Anillina) of New Zealand - Sokolov, Igor M. (Zootaxa, 2015)
Four new species of the formerly monotypic genus Pelodiaetodes are described from New Zealand. Three of them: P. constricticollis, sp. n., P. moorei, sp. n., and P. aldermensis, sp. n., occurring on the North Island, are morphologically similar to the type species, P. prominens Moore. The fourth species, P. nunni, sp. n., occurring on the South Island, is morphologically distinct from the nominotypical species group. A new subgenus, Monosetodes, subgen.n., is proposed to accommodate P. nunni within Pelodiaetodes. Redescriptions of the genus and the type species are given based on new morphological data, and a taxonomic key as well as a distribution map for all known species are provided. Some biogeographical aspects of the evolutionary history of Pelodiaetodes and its morphological relatives from Madagascar, Australia and New Zealand are discussed.